Brain exposure of the ATM inhibitor AZD1390 in humans—a positron emission tomography study. Issue 4 (30th October 2020) - Jucaite, Aurelija; Stenkrona, Per; Cselényi, Zsolt; De Vita, Serena; Buil-Bruna, Nuria; Varnäs, Katarina; Savage, Alicia; Varrone, Andrea; Johnström, Peter; Schou, Magnus; Davison, Chris; Sykes, Andy; et al.
Abstract: Background: The protein kinase ataxia telangiectasia mutated (ATM) mediates cellular response to DNA damage induced by radiation. ATM inhibition decreases DNA damage repair in tumor cells and affects tumor growth. AZD1390 is a novel, highly potent, selective ATM inhibitor designed to cross the blood–brain barrier (BBB) and currently evaluated with radiotherapy in a phase I study in patients with brain malignancies. In the present study, PET was used to measure brain exposure of 11 C-labeled AZD1390 after intravenous (i.v.) bolus administration in healthy subjects with an intact BBB. Methods: AZD1390 was radiolabeled with carbon-11 and a microdose (mean injected mass 1.21 µg) was injected in 8 male subjects (21–65 y). The radioactivity concentration of [ 11 C]AZD1390 in brain was measured using a high-resolution PET system. Radioactivity in arterial blood was measured to obtain a metabolite corrected arterial input function for quantitative image analysis. Participants were monitored by laboratory examinations, vital signs, electrocardiogram, adverse events. Results: The brain radioactivity concentration of [ 11 C]AZD1390 was 0.64 SUV (standard uptake value) and reached maximum 1.00% of injected dose at T max[brain] of 21 min (time of maximum brain radioactivity concentration) after i.v. injection. The whole brain total distribution volume was 5.20 mL*cm −3 . No adverse events related to [ 11 C]AZD1390 were reported. Conclusions: This study demonstrates that [ 11 C]AZD1390 crosses the intact BBB and supports development of AZD1390 for the treatment of glioblastoma multiforme or other brain malignancies. Moreover, it illustrates the potential of PET microdosing in predicting and guiding dose range and schedule for subsequent clinical studies.